Retrograde transvenous obliteration for the prevention of variceal rebleeding in patients with hepatocellular carcinoma: a multicentre retrospective study. Issue 9 (September 2021) - Tsauo, J.; Noh, S.Y.; Shin, J.H.; Gwon, D.I.; Han, K.; Lee, J.M.; Jeon, U.B.; Kim, Y.H.
Abstract : AIM: To evaluate the effectiveness and safety of retrograde transvenous obliteration (RTO) for the prevention of variceal rebleeding variceal rebleeding in patients with hepatocellular carcinoma (HCC). MATERIALS AND METHODS: This multicentre retrospective study enrolled 79 patients with HCC who underwent RTO for the prevention of variceal rebleeding. Successful occlusion of the gastrorenal shunt and obliteration of the gastric varices were achieved in 74 patients, with a technical success rate of 93.7%. Of the remaining 74 patients (mean age, 64.9±10.3 years; 56 men), 66 (90.4%) had gastroesophageal varices and seven (9.6%) had isolated gastric varices. Thirty-two patients (43.8%) underwent balloon-occluded RTO, 40 patients (54.8%) underwent plug-assisted RTO, and one patient (1.4%) underwent coil-assisted RTO. No patients had major procedural complications. RESULTS: Rebleeding occurred in seven patients (9.6%) during the follow-up period. The 6-week and 1-year actuarial probabilities of patients remaining free of rebleeding were 90.8±3.6% and 88.6±4.1%, respectively. The median survival was 12.6 (95% confidence interval [CI] 8–17.3) months. The 6-week, 1-year, and 3-year actuarial probabilities of survival were 83.2±4.4%, 51.1±6.6%, and 32.7±7%, respectively. New or worsening ascites and oesophageal varices occurred in 12 (16.4%) and 13 patients (17.8%), respectively, during the follow-up period. Overt hepatic encephalopathy occurred in one patient (1.4%) during the follow-up period. The Child–Pugh score remained comparable to that at baseline at 1 and 3 months. CONCLUSION: RTO was effective and safe in preventing variceal rebleeding in patients with HCC. Highlights: A rebleeding rate of 9.6% was observed in patients with HCC who underwent RTO. New or worsening ascites and esophageal varices were observed in 16.4% and 17.8%. Macrovascular invasion and HRS were independent negative predictors of survival.